Pendampingan Persiapan Tes SKB CPNS Dosen (Paham tentang Tridharma Perguruan Tinggi sejak Mula) - Eci Sriwahyuni; Adelia Alfama Zamista; Andika Dirsa (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This community service activity aims to increase the knowledge and competence of participants in facing the SKB test, especially in the fields of teaching practice and interviews. The method of this activities is training and mentoring. This activity consists of three stages, namely the stages of preparation, implementation, and reporting. At the preparation stage, the service team conducted a needs analysis with a qualitative approach as the first step for developing service material. At the implementation stage, training was carried out via a zoom meeting with 2 presenters, followed by mentoring via whatsapp group. One of the instruments used in this service is a checklist of learning tools prepared by participants to face the teaching practice test. The results of this PKM activity was known that all participants already knew 3 types of tests on the SKB, knew the grid of test materials, knew the tools that needed to be prepared, and knew about the tridharma of higher education which is one of the main test materials as well as the obligations of lecturers. Â Based on the entries on the checklist, it was also known that participants had been able to find RPS, compile teaching materials and learning media that would be displayed during the teaching practice test. Furthermore, out of ten participants, two have successfully graduated as CPNS in 2021. These results show that the mentoring activities carried out were quite successful.